In Vitro Analysis of Effectiveness Clove Leaf Extract (Syzygium aromaticum) Against Anthracnose Disease (Colletotrichum capsici) on Chili Plants (Capsicum annum L) - Mahendra, Syah Maulana; Abadi, Abdul Latief; Choliq, Fery Abdul (University of Brawijaya, 2022)
Chili (Capsicum annum L) is a plant with a high economic value and is in great demand by the Indonesian people. This research aimed to determine the effectiveness of the difference in the concentration of clove leaf extract in inhibiting anthracnose disease in chili. This research was conducted from February to April 2022. This research used the Complete Randomized Design (CRD) method with six treatments and four replications. The treatment used in this research was the difference in the concentration of clove leaf extract, namely 0%, 1%, 2%, 3%, 4%, and 5%. The research showed that clove leaf extract could inhibit the growth of C. capsici, which caused anthracnose disease in chili. In vitro tests showed that the concentrations of 3%, 4%, and 5% of clove leaf extract significantly differed from all treatments and had fungicidal properties against C. capsici. In conclusion, the research results showed that the effective concentration in inhibiting the growth of C. capsici, which causes anthracnose disease in chili, is the concentration of clove leaf extract 3%, 4%, and 5%.